Nilai Bisnis Implementasi Sistem Informasi Perbankan ICBS (Integrated Computerized Banking System) Pada Bank Danamon Indonesia Tbk. - Lady Diana Warpindyastuti (UNIVERSITAS INDRAPRASTA PGRI, 2020)
As everyone knows, information is one of the important resources that is needed by company management in making decisions. To obtain this information, we need a system that can interpret data into information that is very useful what is called an information system. This information system can make a major contribution to the business value of a company by not only increasing profits but also company productivity. To be able to face the challenges of business and the era of globalization, information systems become the best solution for executives and decision makers to help them in the process of growing and developing companies. One of the most popular information systems is the ICBS (Integrated Computerized Banking System) that has been used by Bank Danamon. By implementing ICBS, Bank Danamon can obtain higher business value so that it can make the company compete in a more competitive business era.This study used descriptive qualitative method.